Good food for bad stomachs - Janowitz, Henry D. (Oxford University Press, 1997)
Every day, in magazines and books, on TV and the radio, we are flooded with advice on what foods to eat. Some of this advice is nonsense--trendy weight-loss regimes, which can actually be harmful--and some is contradictory, as even scientists will vacillate on such subjects as animal versusnonanimal fat, saturated versus unsaturated fatty acids. There are a few good books that cover nutrition in general and even some that tackle specific health goals, such as eating for a healthy heart. But there's no book available on the area of the body most immediately affected by the food weeat--the gastr.